Longer durations of piperacillin/tazobactam treatment cause more prolonged alteration of colonization resistance in mice - Bryan S. Hausman; Claire E. Kaple; Jennifer L. Cadnum; Samir Memic; Naseer Sangwan; Curtis J. Donskey (PLoS ONE, 2026)
Broad-spectrum antibiotics that are excreted into the intestinal tract disrupt microbiota that provide colonization resistance against healthcare-associated pathogens. Minimizing the duration of treatment is a core element of efforts to reduce the adverse effects of antibiotics, but limited information is available on whether this approach preserves colonization resistance. Here, we used a mouse model to examine the impact of 1, 3, 6, and 10-days of treatment with the broad-spectrum antibiotic piperacillin/tazobactam on colonization resistance against vancomycin-resistant Enterococcus faecium (VRE) and carbapenemase-producing Klebsiella pneumoniae at 6-, 10-, and 24-days post-treatment; colonization resistance against Clostridioides difficile was tested at 6 days post-treatment. Colonization resistance was not altered at these time points by 1 day of treatment, whereas 3, 6, and 10 days of treatment caused more prolonged microbiota disruption and altered colonization resistance extending to 6, 10, and 24 days, respectively. In contrast, 5 or 10 days of treatment with aztreonam, a narrow-spectrum antibiotic with no activity against anaerobes, did not alter colonization resistance. These findings provide support for efforts to minimize the duration of antibiotic therapy as longer durations of piperacillin/tazobactam treatment caused greater and more prolonged alteration of colonization resistance. Our results also highlight the potential for short courses of broad-spectrum antibiotics to alter colonization resistance and suggest that selection of antibiotics that cause less disruption of anaerobes may be useful to preserve colonization resistance.